The effect of ACTH4-10Pro8Gly9Pro10 and HMG-CoA reductase inhibitor in moderate head injury: clinical outcome and serum Bcl-2 concentration (Faculty of Medicine Universitas Indonesia, 2013)
Background: An important component of brain tissue damage is apoptotic neuronal death. Bcl-2 is an anti-apoptotic protein, which inhibits the intrinsic pathway of apoptosis. ACTH4-10Pro8Gly9Pro10 and HMG-CoA reductase inhibitor are known for their neuroprotective effects. This study aimed to compare the effect of standard therapy, ACTH4-10Pro8Gly9Pro10, and HMG-CoA reductase inhibitor (simvastatin 40 mg/day) on serum Bcl-2 levels, clinical outcome, and reduction of hospital stay. Methods: Sixty subjects with moderate head injury without any indication for surgery were taken consecutively and separated into three groups: standard treatment only (control group), standard treatment combined with ACTH4-10Pro8Gly9Pro10, and standard treatment combined with inhibitor of HMG-CoA reductase. Blood samples were taken on day-1 and day-5 from each subject for measurement of Bcl-2 concentration. Barthel Index and MMSE were measured at discharge and hospital length of stay was noted. Difference in mean was analyzed with one way ANOVA and correlation between Bcl-2 and clinical outcome was measured with Pearson correlation test. Results: Bcl-2 serum levels on day-1 and day-5 were tespectively as follows: in control group were 1.39 ± 0.75 and 1.48 ± 0.77 ng/mL; in ACTH4-10Pro8Gly9Pro10 group 1.39 ± 0.70 and 3.70 ± 1.01 ng/mL which was significantly higher compared to other groups and associated with the shortest length of stay. In simvastatin group, 1.53 ± 0.55 and 2.17 ± 0.56 ng/mL. We found the length of stay in the ACTH4-10Pro8Gly9Pro10 group to be significantly shorter (p < 0.001). The correlation of clinical outcome (Barthel index and MMSE) with serum Bcl-2 levels was not significant. Conclusion: ACTH4-10Pro8Gly9Pro10 significantly increased serum Bcl-2 concentration in head injury and associated with shorter length of stay. An increase of serum Bcl-2 concentration was also found in simvastatin group, but it was not significant. (Med J Indones. 2013;22:221-6. doi: 10.13181/mji.v22i4.604)